Acoso escolar - medidas de prevención y actuación = Harrassment at school: measures of prevention and performance - Gómez, Juana María Rodríguez (Educação)
The violence in the scholastic centers and, more concretely, the harassment scholastic, es not a new phenomenon. However, they have been the serious facts that we are knowledge in the day to day those that have been sensitizing the society, of such form, that first opinion “is things of children” has been replaced by another one. This recognizes the consequences that can entail for an adolescent a situation of harassment. It is necessary to sensitize the teaching staff, pupils and families of the consequences of I mistreat between you equal. In this definitive article, the harassment scholastic. We establish the levels of prevention and performance in the educative centers